Impact of simulated brain interstitial fluid flow on the chemokine CXCL12 release from an alginate-based hydrogel in a new 3D in vitro model - El Kheir, Wiam; Dumais, Anaïs; Beaudoin, Maude; Marcos, Bernard; Virgilio, Nick; Paquette, Benoit; Faucheux, Nathalie; Lauzon, Marc-Antoine (Frontiers in Drug Delivery, 2023)
Drug delivery systems have been widely studied in glioblastoma multiforme (GBM) disease. The GBM cells high infiltrative pattern in the brain depends on their structural heterogeneity, the interstitial fluid flow (IFF) and chemokines. A sustained release gradient of CXC-chemokine-ligand-12 (CXCL12) can be used as a therapeutic approach to control the dissemination of GBM cells. Hydrogels are known for their capability to encapsulate different agents and control their release. In the present study, the release kinetics of CXCL12 (free or encapsulated into nanoparticles) from alginate-based hydrogels were determined under static and dynamic conditions. We first demonstrated that the release kinetic profiles under static culture conditions were independent of the initial mass loading and the predominant This is a provisional file, not the final typeset article phenomenon occurring was diffusion. Thereafter, the release of CXCL12 loaded into Alginate/Chitosan-Nanoparticles (Alg/Chit-NPs) and embedded into alginate-hydrogel was determined. Results of the mathematical modeling showed the presence of electrostatic interactions between alginate and CXCL12. The Alg/Chit-NPs allowed to slow down the burst release of the molecule resulting in a decrease in the diffusion coefficient. We then developed a 3D in vitro model recapitulating the peritumoral environment that mimics the brain IFF for studying the convective contribution of simulated IFF on CXCL12 release. For the different fluid flows assessed, 0.5 µL/min, 3 µL/min, 6.5 µL/min and 10 µL/min, the cumulative proportions of CXCL12 released increased as the flow rate increase for the three initial mass loadings. Above 3 µL/min, convection was the main mechanism dominating CXCL12 release whereas, below it, diffusion takes the lead. The indirect perfusion flow had a crucial impact on CXCL12 release and distribution inside the hydrogel in and against its direction. This system highlights the importance of considering the IFF in brain targeting delivery system and will be used in the future to study GBM cell behaviors in response to CXCL12 gradient. a mis en forme : Justifié a mis en forme : Italien (Italie) a mis en forme : Français (Canada) a mis en forme : Italien (Italie) a mis en forme : Français (Canada)